FRI0213 The performance of 12 flare definitions including the assessment of spondyloarthritis international society (ASAS)-endorsed definition of clinically important worsening in asdas in patients with axial spondyloarthritis treated with adalimumab for 5 years. (12th June 2018) - Juhl Pedersen, S.; Sørensen, I.J.; Loft, A.G.; Hindrup, J.; Kollerup, G.; Thamsborg, G.; Asmussen, K.; Hendricks, O.; Nørregaard, J.; Østergaard, M.
Abstract : Background: In 2016 the Assessment of Spondyloarthritis International Society (ASAS) published proposals for 12 definitions of ′flare′(ref. 1) for patients with axial spondyloarthritis (axSpA). The definitions are based on pain, BASDAI and ASDAS (see table 1). In January 2018, ASAS published the ASAS-endorsed definition of clinically important worsening based on ASDAS (ΔASDAS≥0.9)(ref. 2). Objectives: The aim of this study was to describe the frequency of ′flares′ as detected by the 12 flare definitions including the ASAS-endorsed definition. Methods: Data from an investigator-initiated double-blinded randomised placebo-controlled trial of adalimumab versus placebo of 12 weeks with a 5 year open-label extension (NCT00477893, ref. 3) were used for this study. The number of patients experiencing a flare at each visit according to the 12 ASAS ′flare′ definitions was recorded for 20 study visits performed from two weeks after initiation of treatment and to year 5. Results: 52 patients started treatment and 41 (79%) patients completed the 5 year follow-up visit. The total number (percentage) of study visits where pain, BASDAI and ASDAS flares could be calculated was 879 (84.5%), 875 (84.1%) and 842 (81.0%), respectively. The mean (SD) number of patients with a flare per visit ranged from 0.7 (1.2) to 3.8 (2.2) and the median (inter-quartile-range (IQR)) from 0 (0–1) to 5(3–7) (table 1). The mean number of patients per visit with a flare was significantly higher when the definition "change in ASDAS≥0.6" (p<0.0001 to p=0.001, t-test) and "change ASDAS≥0.6 AND observed ASDAS≥1.3" (p<0.0001 to p=0.04) were applied, and the mean number of patients was significantly lower when the BASDAI flare definitions were applied (p<0.0001 to p=0.02). Conclusions: The frequency of flares as detected by the 12 ASAS flare definitions for patients with axial spondyloarthritis differed substantially. The ASAS-endorsed definition performed well. References: [1] Gossec, et al. Ann Rheum Dis2016;68(2):418–29. [2] Molto, et al. Ann Rheum Dis. 2018;77(1):124–127. [3] Pedersen, et al. Arthritis Rheumatism2016;68:418–29. Disclosure of Interest: None declared